Electrocardiographic Changes in patients with Acute Febrile Illness: A Cross-Sectional Study in a Tertiary Care Hospital - Saeed Maqsood, Sadullah Shah, Naimat Ullah Shah, Samiullah Khan, Radhia Khan, Muhammad Saad Jibran (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute febrile illnesses (AFI) are frequent causes of hospitalization and can influence any body system, including the heart. Even in patients who do not have pre-existing cardiac disease, electrocardiographic (ECG) alterations can be an indication of systemic inflammation, autonomic imbalance, or myocardial involvement that is subclinical. Monitoring and control can be directed using early identification of these changes. Objective: To identify the rate and trend of changes in electrocardiograph in patients who present with acute febrile illness at a tertiary care hospital. Materials and methods: The study was a cross-sectional study carried out at Medical Teaching Institution Bannu and Medical Teaching institution DI Khan during the period between July 2022 and December 2022. Enrolment was restricted to adult patients who were found to be having fever 38C or lower of less than two weeks. The patients who had known cardiac disease or those on medications that affect ECG were excluded. Qualified clinicians recorded and interpreted standard 12-lead ECGs. The descriptive and inferential statistics were used to gather and analyze the demographic, clinical and ECG data. Results: 180 patients were used (mean age 38.6 +14.2 years 60 men). In 96 (53.3) patients, the abnormalities of the ECG were observed. Sinus tachycardia (30, 11.7, and 10 percent of abnormalities respectively) was the most common and ST-segment alterations, T-wave inversion, and QT interval prolongation were the third, fourth, and fifth most common abnormalities respectively. Abnormalities in ECG were more apparent among the patients above 40 years old and a little more in males. Other less frequent discoveries were sinus bradycardia and conduction defects. Conclusion: Electrocardiographic alterations are frequent in acute febrile disease, and the sinus tachycardia and repolarization changes are most frequent. Febrile patients may undergo periodic ECG examination, which could potentially aid in identifying subclinical cardiac involvement and manage the patient. Keywords: Acute febrile disease, Electrocardiography, Cardiac abnormalities, Sinu tachycardia.